Liposarcoma of the scalp mimicking a lipoma: a case report - Subha, Sethu Thakachy; Sanjurjo, Andrea; Poyet, Karen Masterson; Marchal, Francis (SpringerOpen, 2022)
Background: Liposarcomas are malignant tumours of adipocytic differentiation and their occurrence within the head and neck region is very uncommon. Lipomas are the most common types of benign mesenchymal tumours. The clinical, histological and imaging features of well-differentiated liposarcoma may resemble that of lipoma, causing challenges in the diagnosis. The management and prognosis of benign lipomas and well-differentiated liposarcoma are different. Case presentation: A 73-year-old man presented with a painless soft mass in the left temporal region for 15 years with recent rapid growth. The scalp mass was clinically diagnosed as lipoma, while MRI suspected an atypical lipomatous lesion. Complete surgical resection was performed, and histopathological examination confirmed a well-differentiated liposarcoma. The patient recovered completely and will be followed up with long-term surveillance. Conclusion: This report is to highlight that clinicians must have a high index of suspicion for this rare entity when dealing with scalp masses and suspicious radiological findings, which can affect the overall management and prognosis.